2017
DOI: 10.1016/j.neuroimage.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Higher locus coeruleus MRI contrast is associated with lower parasympathetic influence over heart rate variability

Abstract: The locus coeruleus (LC) is a key node of the sympathetic nervous system and suppresses parasympathetic activity that would otherwise increase heart rate variability. In the current study, we examined whether LC-MRI contrast reflecting neuromelanin accumulation in the LC was associated with high-frequency heart rate variability (HF-HRV), a measure reflecting parasympathetic influences on the heart. Recent evidence indicates that neuromelanin, a byproduct of catecholamine metabolism, accumulates in the LC throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 58 publications
6
62
1
1
Order By: Relevance
“…It is thus possible that LC signal intensity might reflect the habitual LC activation in young adults. Consistent with this hypothesis, greater LC signal intensity was associated with reduced high frequency heart rate variability, a measure reflecting parasympathetic influences on heart rate, in healthy adults . We thus postulated that repeated LC activation during MWA attack in young adults would result in heightened LC signal intensity compared to healthy controls.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…It is thus possible that LC signal intensity might reflect the habitual LC activation in young adults. Consistent with this hypothesis, greater LC signal intensity was associated with reduced high frequency heart rate variability, a measure reflecting parasympathetic influences on heart rate, in healthy adults . We thus postulated that repeated LC activation during MWA attack in young adults would result in heightened LC signal intensity compared to healthy controls.…”
Section: Discussionmentioning
confidence: 55%
“…We did not assess anxiety and depression in included patients/controls, which may be a limitation. Indeed, a previous study showed a weak correlation of LC contrast with anxiety and depression in healthy subjects, which, however, was no longer significant after adjustment in multivariate analysis . Another study reported a reduced LC signal in depression .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations